Normative data on the foveal avascular zone in a young healthy Irish population using optical coherence tomography angiography. Issue 5 (September 2022) - O'Shea, Susan M.; O'Dwyer, Veronica M.; Scanlon, Grainne
Purpose: To establish normative data on the size, shape and vascular profile of the foveal avascular zone (FAZ) in a young, healthy, Irish population, using the Cirrus 5000 HD-OCT. Certain diseases may alter FAZ appearance. Normative databases provide normal baseline values for comparison, thus improving diagnostic ability. Methods: One hundred and fifty-four subjects aged 18–35 years old were recruited. Superficial FAZ area, diameter, circularity, ganglion cell layer, central macular thickness (CMT), vascular perfusion and density were measured using the Cirrus 5000. Axial length was measured with the IOL Master and blood pressure was measured using the Omron sphygmomanometer. Results: Mean FAZ area was 0.22 ± 0.07 mm 2, mean CMT was 263.08 ± 18.73μm. Both were larger in females than males (p = 0.022, p = 0.000). Mean vessel density and perfusion central were 14.11 ± 2.77 mm/mm 2 and 24.70 ± 4.96% respectively. Both were lower in females (p = 0.010, p = 0.019). Vessel density and perfusion inner correlated positively with minimum ganglion cell layer plus inner plexiform layer (GCL + IPL) thickness (p = 0.001, p = 0.019). CMT correlated positively with vessel density and perfusion central (p = 0.000 for both) and negatively with FAZ area (p = 0.000). Conclusions: This study provides normative data for FAZ appearance and vascularity for the first time in a young, healthy, Irish population, using the Cirrus 5000 HD-OCT. Establishing machine and population specific normative data, particularly in relation to vessel density and perfusion is paramount to the early identification of ocular disease using Optical Coherence Tomography Angiography.